2021
DOI: 10.1002/admi.202100489
|View full text |Cite
|
Sign up to set email alerts
|

Strong Coupling of Colloidal Quantum Dots via Self‐Assemble Passivation for Efficient Infrared Solar Cells

Abstract: The surface passivation of colloidal quantum dots (CQD) is critical for the electronic coupling of CQDs, which significantly affects the photovoltaic performance of CQD solar cells (CQDSCs). Herein, a self‐assemble passivation (SAP) strategy of CQDs is introduced to improve CQD coupling. The PbI2 passivation layer prepared using the SAP method can largely improve surface defect passivation of CQDs, diminishing charge recombination induced by the sub‐bandgap traps. Meanwhile, extensive theoretical simulations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…26 Recent work has shown that the binding energy of the core level Pb 4f spectrum will shift to a higher energy in the presence of PbI 2 on the PbS QD surface. 38 We also found that the binding energy of the Pb 4f core level peak in the PbAc-MAAc film shifts to a higher energy toward the reference PbI 2 peak position, consistent with the interpretation that MAPbI 3−x Ac x decomposes upon heating, leaving behind PbI 2 in the QD film (see Figure S6). SWIR Photodiode Performances.…”
Section: ■ Results and Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…26 Recent work has shown that the binding energy of the core level Pb 4f spectrum will shift to a higher energy in the presence of PbI 2 on the PbS QD surface. 38 We also found that the binding energy of the Pb 4f core level peak in the PbAc-MAAc film shifts to a higher energy toward the reference PbI 2 peak position, consistent with the interpretation that MAPbI 3−x Ac x decomposes upon heating, leaving behind PbI 2 in the QD film (see Figure S6). SWIR Photodiode Performances.…”
Section: ■ Results and Discussionsupporting
confidence: 86%
“…As shown in Figure a, the absence of the nitrogen peaks in the XPS spectra confirms the thermal decomposition of MAPbI 3– x Ac x as the presence of MA cations should be associated with the nitrogen peaks in the XPS spectra . Recent work has shown that the binding energy of the core level Pb 4f spectrum will shift to a higher energy in the presence of PbI 2 on the PbS QD surface . We also found that the binding energy of the Pb 4f core level peak in the PbAc-MAAc film shifts to a higher energy toward the reference PbI 2 peak position, consistent with the interpretation that MAPbI 3– x Ac x decomposes upon heating, leaving behind PbI 2 in the QD film (see Figure S6).…”
Section: Resultssupporting
confidence: 75%
“…Due to the combined advantages of perovskites and quantum dots (QDs), such as low cost, solution processability, tunable bandgap energy (E g ) and high stability [1][2][3][4][5][6][7][8][9], perovskite QDs (PQDs) have received increasing attention for application in light-emitting diodes [10,11], photodetector [12][13][14], and solar cells [15,16]. Since the first PQD solar cells (PQDSCs) were successfully fabricated by Swarnkar et al in 2016 [17], with the material synthesis improvement [18][19][20], post-treatment of PQDs [21][22][23][24][25], and tuning device structure of solar cells [26][27][28][29], the performance of inorganic CsPbI 3 PQDSCs has considerably improved.…”
Section: Introductionmentioning
confidence: 99%
“…CQDs were synthesized using a modified Schlenk line process in a nitrogen atmosphere 16 . Pb(AC)2 (1.55 g), OA (3 mL), and ODE (20 mL) were added to a flask (250 mL).…”
Section: Ligand Exchange Of Pbs Cqdsmentioning
confidence: 99%
“…Colloidal quantum dot (CQD) is one of the most competitive infrared optoelectronic materials for emerging infrared applications [1][2][3] , such as photodetectors [4][5][6][7] , light-emitting devices (LEDs) [8][9][10] , and solar cells [11][12][13][14][15][16] , due to its strong infrared absorption, high stability, solution processibility and sizedependent bandgap energy [17][18][19][20][21] . In particular, for photovoltaic applications, the multi-exciton generation (MEG) of the CQD makes it possible to break through the Shockley-Queisser efficient limitation of single-junction solar cells that more than one electron-hole pair could be produced after absorption of one high energy photon 22,23 .…”
mentioning
confidence: 99%